Effects of dry season nutritional supplementation on growth, onset of puberty and subsequent fertility in Boran and Boran X Friesian heifers in Ethiopia - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (Elsevier, 1992)
Presents results of a trial undertaken in Ethiopia to determine the effect of dry season supplementary feeding on heifers' growth rate & fertility at puberty, hence at 8 months of age, 43 Boran and 46 Boran X Friesian crossbred heifers were randomly divided to either receive a supplementary feed containing 16 percent crude protein during the dry season or to serve as controls. The heifers were examined monthly and data on body weight, wither height and body condition score were recorded, also ovarian size and structures were determined per rectum and heifers were kept under continuous observation for standing heat, and blood samples were collected at 10-day intervals every month to determine plasma progesterone levels, and all heifers were exposed to intact bulls for 4 months after 18 months of age.